Holding still, together Parkinson in Beeld - Stap, Thieme (Radboud University Press, 2022)
This book provides unique insights into how health professionals and people with Parkinson's disease shape care together. It shows both the courage and vulnerabilities of those who have to face this disease. It consists of photos of people with Parkinson's disease and their care professionals, both of their interaction and portrayed individually, interwoven with fragments of their dialogue about meaningful care. This book is an integral part of a research project at Radboud university medical center into person-centred care. With it, we hope to contribute to a positive, hopeful vision of ever-improving Parkinson's care.